A multistate open robust design: population dynamics, reproductive effort, and phenology of sea turtles from tagging data. Issue 1 (29th August 2018) - Kendall, William L.; Stapleton, Seth; White, Gary C.; Richardson, James I.; Pearson, Kristen N.; Mason, Peri
Abstract: Understanding population dynamics, and how it is influenced by exogenous and endogenous factors, is important to the study and conservation of species. Moreover, for migratory species, the phenology and duration of use of a given location can also influence population structure and dynamics. For many species, breeding abundance, survival, and reproductive performance, as well as phenology of nesting, are often the most accessible, and therefore, practical elements of their life history to study. For a population of hawksbill sea turtles ( Eretmochelys imbricata ), we modeled population change for nesters and total adult females, survival, and breeding probability, from 25 yr of intensive tagging data. We modeled breeding probability as a function of the number of years since last breeding and tested for differences between neophyte and experienced nesters. For each year, we also estimated the number of clutches deposited per female, and phenology of use, for neophytes and experienced nesters. To implement the analysis, we developed a novel generalized multistate open robust design mark–recapture modeling framework, with parameters for survival and transition probabilities, and for each primary period, state structure and arrival, persistence, and detection probabilities. Derived parameters included abundance of observable and unobservable components of the population, residence time, expected arrival and departure periods, and per‐period intensity of study area use. Abundance of nesters increased over most of the time series. Survival probability was 0.935 ± 0.01 (estimate ± SE). Virtually all hawksbills skipped at least one year of nesting. Breeding probability increased by skipping a second year, but then decreased thereafter. Subsequent breeding probability was lower for neophyte nesters than for experienced nesters, but the effect was weaker than the effect of years since breeding. Clutch frequency varied by year, with no discernable pattern of differences between neophytes and experienced nesters. Mean arrival and departure dates also varied, with a slight shift of nesting activity to earlier in the season. The multistate open robust design model developed here provides a flexible framework for modeling the dynamics of structured migratory populations and the phenology and duration of their seasonal use of study areas.